Differential sex, morphotype and tissue accumulation of mercury in the crab Carcinus maenas - Costa, Sónia (2019)
Carcinus maenas is an invasive species of recognised economical and ecological importance in which mercury accumulation could be a pathway for bioamplification through food webs. Little information is available about differential accumulation between crab sexes and morphotypes. Taking this in mind, a set of different industrial discharge scenarios were investigated in 96-h laboratory experiments for assessing the accumulation of inorganic mercury from contaminated seawater into the tissues of C. maenas. Three groups of crabs (green males, green and red females) where exposed to 5, 50 and 250 μg Hg L −1. Differences among sexes, morphotypes and tissues were detected, depending on the mercury concentration. The muscle did not show differential accumulation between sexes or morphotypes. For mercury exposed crabs, the contaminant was accumulated preferably in the gills (more than 75%) while, in control experiments, it was in the internal organs, muscle and hepatopancreas, and gills corresponded to less than 31% of the total mercury quantified. The different tissue contamination seems dependent on the major pathway of exposure, diet or water. Mercury accumulation by the crab was a rapid process and could represent a risk for the environment only after 96 h. In a scenario of a discharge point of 250 μgL −1, all tissues of crabs exposed would attain a very close, or even exceed the threshold concentration value for human consumption (0.5 mg kg−1).